Academic Success and Stories of Resiliency: African American Female Students Navigating the College Terrain - Theresa White; Paola Nava Jimenez; Anna Beatriz Guerrero (International Journal of Education, 2024)
Many educators have become accustomed to using the deficit model of thinking to illustrate the challenges faced by African American students, frequently interpreting their academic struggles as personal failures and lack of resilience. In 2007, a public university in Southern California established the Learning Habits Project (LHP), a study designed to assess the ongoing efforts of university academic programs and to provide data on fostering student success through successful learning habits. This study documented the strategic approaches that foster academic success and resilience employed by 19 African American female college students. Viewed through the lens of Black Feminist Standpoint and Resiliency theories, the results of this study can be used to guide students and educators seeking to improve academic success and resiliency in higher education.